2014
DOI: 10.1007/s00270-014-1041-8
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Irreversible Electroporation of a Large Centrally Located Hepatocellular Adenoma in a Woman with a Pregnancy Wish

Abstract: Irreversible electroporation (IRE) is a novel image-guided ablation technique that is rapidly gaining popularity in the treatment of malignant liver tumors located near large vessels or bile ducts. We describe a 28-year-old female patient with a 5 cm large, centrally located hepatocellular adenoma who wished to get pregnant. Regarding the risk of growth and rupture of the adenoma caused by hormonal changes during pregnancy, treatment of the tumor was advised prior to pregnancy. However, due to its central loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…PEF treatment has dramatically improved gene-transfer efficiencies in tissues such as liver, skin, and skeletal muscle [22,38,39,40]. IRE technology has been used to treat tumors in canine brain tissue [41], human and porcine liver tissue [42,43,44,45], and and human and porcine pancreatic tissue [46,47,48]. By destroying malignant cells while mitigating damage to critical stromal tissue components [49,50], it enables the treatment of tissues around critical structures that would otherwise render the site untreatable.…”
Section: Introductionmentioning
confidence: 98%
“…PEF treatment has dramatically improved gene-transfer efficiencies in tissues such as liver, skin, and skeletal muscle [22,38,39,40]. IRE technology has been used to treat tumors in canine brain tissue [41], human and porcine liver tissue [42,43,44,45], and and human and porcine pancreatic tissue [46,47,48]. By destroying malignant cells while mitigating damage to critical stromal tissue components [49,50], it enables the treatment of tissues around critical structures that would otherwise render the site untreatable.…”
Section: Introductionmentioning
confidence: 98%
“…Integral muscle relaxation is also essential which implies the use of curare and by definition, general anesthesia. Limited severe collateral damage has been seen to date in patients generally selected on the basis of tumor sites deemed to be ''at risk'' for the other thermal methods [7,8].…”
Section: Electroporation: When Thermo-ablation Is Too Riskymentioning
confidence: 99%
“…32 There are limited reports regarding the ablative effects of HCA (Table 6). [33][34][35][36][37] Rocourt et al 33 reported a 13-year-old patient in whom a liver tumor measuring 35 mm was incidentally detected and was histologically diagnosed as adenoma by percutaneous biopsy. 33 Because of the relatively small lesion, RFA was selected as the treatment of choice.…”
Section: Hepatocellular Adenoma (Hca)mentioning
confidence: 99%